2020
DOI: 10.3390/languages5040068
|View full text |Cite
|
Sign up to set email alerts
|

Gender in Unilingual and Mixed Speech of Spanish Heritage Speakers in The Netherlands

Abstract: This study examines heritage speakers of Spanish in The Netherlands regarding their production of gender in both their languages (Spanish and Dutch) as well as their gender assignment strategies in code-switched constructions. A director-matcher task was used to elicit unilingual and mixed speech from 21 participants (aged 8 to 52, mean = 17). The nominal domain consisting of a determiner, noun, and adjective was targeted in three modes: (i) Unilingual Spanish mode, (ii) unilingual Dutch mode, and (iii) code-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Variation at the individual level has been observed by Boers et al (2020) andvan Osch et al (2022), who demonstrate that differences between speakers with respect to gender agreement strategies in code-switching are related to differences in dominance, in terms of proficiency, use and exposure. Similarly, Liceras et al (2008) and Munarriz-Ibarrola et al (2022) report differences in code-switching patterns between groups of bilinguals that seem to be related to the order of acquisition of the languages in the particular bilingual group.…”
Section: Extra-linguistic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Variation at the individual level has been observed by Boers et al (2020) andvan Osch et al (2022), who demonstrate that differences between speakers with respect to gender agreement strategies in code-switching are related to differences in dominance, in terms of proficiency, use and exposure. Similarly, Liceras et al (2008) and Munarriz-Ibarrola et al (2022) report differences in code-switching patterns between groups of bilinguals that seem to be related to the order of acquisition of the languages in the particular bilingual group.…”
Section: Extra-linguistic Factorsmentioning
confidence: 99%
“…Nevertheless, "no clear evidence has emerged concerning the structural regularities that underlie mixed speech across language pairs, or even within the same language pair in different communities" (Parafita Couto et al, 2023). Recent studies suggest that different codeswitching strategies may be used between members of the same community (e.g., Boers et al, 2020) and also that there are crosscommunity differences between communities that share the same language combinations, suggesting that sociolinguistic variables may in some cases override structural constraints. However, to date, we still do not have a clear picture of how the interaction of different linguistic and extralinguistic components shapes code-switching outcomes (Stell and Yakpo, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important factor to explain the production of N-SGA in this study is the use of the masculine default gender, an important variable in other previous studies (e.g., Balam et al, 2021). However, it was interesting to note that, contrary to other studies analyzing N-SGA in other language contact situations (e.g., Alarcón, 2011;Bianchi, 2012;Boers et al, 2020;Goebel-Mahrle and Shin, 2020;Ramírez Cruz, 2009), the majority of the antecedents with which speakers produced N-SGA ended with their corresponding canonical vowel.…”
Section: Discussionmentioning
confidence: 62%
“…Various work has found that HS children tend to over-extend the default gender more so than do their monolingual peers (Sanchez-Sadek et al, 1975;Anderson, 1999;Montrul and Potowski, 2007;Cuza and Pérez-Tattam, 2015). These patterns persist into adulthood, and manifest in divergent production and comprehension of gender agreement, as mentioned above (Montrul et al, 2008;Alarcón, 2011;Boers et al, 2020;Hur et al, 2020). Although a substantial portion of the literature on gender in heritage languages has focused on the heritage gender system in the environment of a dominant language that lacks grammatical gender (i.e., English; cf.…”
Section: Background Grammatical Gender In Heritage Languagesmentioning
confidence: 95%